Planting Seeds of Change in Foodstyles: Growing Brand Strategies to Foster Plant-Based Alternatives Through Online Platforms - Gino Gabriel Bonetti; Chelsea van Hooven; Maria Giovanna Onorati (Gastronomy)
This article delves into the landscape of the plant-based food industry, exploring innovative market entry strategies and their interplay with the evolving food market and shifting consumer preferences and lifestyles. Adopting a multidimensional approach, the study reflects diverse perspectives at play. Through a comparative analysis of strategic promotion and growth strategies employed by both innovative startups and established industry giants in the plant-based alternatives sector in Germany, the study aims to capture the challenges faced by the ‘newer’ wave of plant-based alternatives. This examination is particularly relevant for navigating the complexities of entering a competitive market. Striving to penetrate evolving consumer lifestyles, the study draws insightful comparisons with their “older” counterparts. In addition, through in-depth interviews with selected companies, the study investigates the entry methods of startups venturing into the German market, aiming to identify parallels and contrasts in market strategies with established brands. This provides valuable insights into innovation within the alternative food market. Furthermore, the study explores the process of brand “platformization” by scrutinizing the websites of the selected companies and analyzing customers’ online reviews of their brand experience. This comprehensive analysis unveils distinctive patterns in communication strategies, brand positioning, and consumer engagement, offering insights into the ways plant-based innovation shapes new, caring lifestyles. The main findings include a strong correlation among dimensions related to food quality, use, and taste, indicating a holistic approach to food consumption facilitated by online platforms.